Who can afford a 'livable' place? The part of living global rankings leave out. Issue 1 (2nd January 2021) - Cramer-Greenbaum, Susannah
ABSTRACT: As global livability rankings gain press attention and powerful influence with policy makers, we need an expanded critical debate on their context and problems. This essay narrates a brief history of three influential global livability rankings and critiques several major flaws in their criteria. We demonstrate how both Mercer and EIU's business model dictates an artificial split between livability and the cost of living that has permeated current popular conceptualisations of livability, and focus on the lack of housing affordability as a ranking criterion. This essay evaluates top-ranked cities against perceptive and quantitative measures of housing cost, and shows how many of these cities share extremely high housing cost burdens. A just city should provide housing opportunities for all residents, not just the global elite for whom livability rankings were initially designed. Livability rankings, as currently conceptualised, distract from that goal.